Penerapan Usaha Sandblasting Untuk Meningkatkan Daya Saing Bengkel Motor Di Desa Bugangan - Harmoko; Hakim, Mujibul; Faza, M. Dzikrullah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
One of the livelihood businesses of the Bugangan villagers is a motorcycle repair shop. This business usually only provides light service services, oil changes, and replacement parts spare. The location of the motorbike repair shop in Bugangan village is not strategic because it is on a village road and not too busy with vehicles passing by. There are additional innovations in the motorbike repair shop in Bugangan village so that they can compete and increase income, such as sandblasting services. Sandblasting is cleaning metal surfaces due to dirt (paint, corrosion) with abrasive materials using a compressor. If you use sandblasting, of course, it will be faster and cleaner on the surface of the workpiece. This service aims to form partners into unique and attractive workshops, ready-to-face competition, and increase partner income. In contrast, implementing the service starts with making sandblasting tools, socializing using sandblasting tools, and K3 and creating online and offline marketing. The results of the service implementation are sandblasting tools, manual tool books, and digital marketing. Limitations in this service include partner mastery of tool technology still needs improvement. The contribution of the sandblasting device to the workshop provides an alternative for cleaning dirt on metal and narrowing gaps in the metal.